KELAYAKAN FINANSIAL USAHAPETERNAKAN AYAM RAS PETELUR ISA BROWN (Studi Kasus pada UD. Aditya di Kecamatan Penebel, Kabupaten Tabanan, Bali) - Widiastra Km.; I W. Sukanata; B. R. T. Putri (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2019)
The study aims to determine financial feasibility and Break Even Point of laying chicken farm business was carry outfrom June 2018 to July 2018 at UD. Aditya located in Penebel District, Tabanan Regency, Bali Province. The data used are primary and secondary data was analyzed with analysis of investment criteria Pay Back Period, Break Even Point¸ and sensitivity analysis.This study indicated that laying chicken farm business resulted in NPV 1,943,774,054.91, IRR 19.7%, and Net B / C 1.34.Pay Back Periodwas achieved in time of 1.85 years whileBreak Even Pointwas achieved in time of 7.92 years, Break Even Pointegg production can be achieved when the amount of production 3,102,537.02 eggs/year, or when the price of eggs Rp. 1.191.28/egg.Laying chicken farm business is sensitive to the increase of feed price which was equal to 14.47% and very sensitive to the decrease in egg price by 8.36%. It can be concluded that the laying chicken Isa Brown farm owned by UD. Aditya was financially feasibled. Keywords: laying chicken, financial feasibility, investment criteria, sensitivity